Biochar impacts on soil properties : A review focusing on Nordic research - Hyväluoma, Jari; Tähtikarhu, Mika; Rasa, Kimmo (Scientific Agricultural Society of Finland, 2026)
Biochar used as a soil amendment has been reported to influence crop productivity and the environmental impacts of agriculture. The impacts are challenging to generalize, as they depend on regional farming and climatic conditions. We collected and synthesized the scattered research findings from Fennoscandian countries to increase understanding of biochar impacts (crop yield, soil hydraulic properties, soil structural stability, and carbon storage) in high-latitude agricultural soils. The influence of biochar was generally minor, with only a few sporadic clearly positive indications. While the number of study cases was too small to draw indisputable conclusions, low-fertility soils could be potential targets for biochar in boreal conditions. Also, global meta-analyses show the greatest yield increases in coarse-textured, nutrient-poor, and acidic soils. Such agricultural soils are, however, a minority in the Fennoscandian conditions, which calls for further systematic investigations on biochar application on non-arable soils. The synthesized experimental results indicate that biochar has the potential to increase the long-term soil carbon storage. Our review highlights the scarcity of long-term investigations into the effects of biochar ageing and, consequently, soil properties. Several field experiments set up over a decade ago could provide a sound basis for research focusing on biochar ageing.
Keywords: soil amendment; soil hydraulic properties; aggregate stability; carbon storage; greenhouse-gas emissions